Effect of humic acid on E. coli disinfection in a microbubble-gas plasma reactor. (October 2019) - Wright, Alexander; Uprety, Bipin; Shaw, Alex; Shama, Gilbert; Iza, Felipe; Bandulasena, Hemaka
Abstract: Final effluent from wastewater treatment plants may contain bacteria that can pose a range of environmental and health threats. A microbubble-gas plasma reactor capable of producing a number of both reactive oxygen species and reactive nitrogen species has been developed for inactivating bacteria in final effluents. At the optimum operating conditions, greater than 5-log reductions in E. coli viability was achieved in pure water after 30 min of operation with an energy consumption of 68 kJ/L. Addition of humic acid reduced the E. coli inactivation rate. At the highest concentration of humic acid tested (0.0015% w/w), E. coli inactivation was reduced by ˜50% compared to that achieved in pure water for a 30-minute treatment time. Longer treatment times may be required for waste streams having a high organic content, but the disinfection levels achieved with a low power consumption demonstrate the potential of this approach for industrial use.